The impact of swimming coaches’ authentic leadership coaching on trust, self-efficacy, service quality, and relationship continuity intention - Kim, Buom (Frontiers in Psychology, 2025)
PurposeThis study investigates how swimming coaches’ authentic leadership influences trust, self-efficacy, service quality, and relationship continuity intention among adult recreational swimmers in South Korea. Using structural equation modeling (SEM), it aims to provide insights for enhancing leadership practices in community sports.MethodsA total of 280 adult recreational swimmers participated in the survey, using validated scales on a 5-point Likert scale. Structural equation modeling and bootstrapping with 5,000 resamples were employed to analyze the relationships among authentic leadership, trust, self-efficacy, service quality, and relationship continuity intention.ResultsThe SEM analysis demonstrated excellent model fit (χ2/df = 2.41, CFI = 0.95, TLI = 0.94, RMSEA = 0.059). Authentic leadership significantly influenced coach trust, which in turn positively affected self-efficacy and service quality. While Hypothesis 4 (coach trust → relationship continuity intention) was not supported, mediation analysis showed that self-efficacy and service quality significantly mediated the relationship, indicating that trust indirectly sustains participants’ continuity intention.ConclusionAuthentic leadership plays a vital role in fostering trust, self-efficacy, and service quality in community sports programs. These factors indirectly support participants’ sustained engagement, highlighting the importance of leadership development in enhancing the effectiveness of community-based swimming programs.